Mechanical properties of copper processed by Equal Channel Angular Pressing – a review (Fracture and Structural Integrity, 2011)
The Equal Channel Angular Pressing is a hardening treatment with which ductile metals can beprocessed to refine their grain and sub-grain structure. This process enhances the mechanical strength of metalsin terms of tensile strength, stress-controlled fatigue strength, and fatigue crack growth resistance. In this paperthe authors draw a review of the major results of a wide research activity they carried out on a coppermicrostructure processed by Equal Channel Angular Pressing. The essential results are that tensile and fatiguestrengths of the so obtained refined structure are improved by a factor of two with respect to the originalcoarse-grained metal. The fatigue crack initiation mechanism and the stability of the refined microstructureunder cyclic loading are topics also discussed, evidencing the essential role of the process and of the materialparameter, as the content of impurities in the microstructure. In this review, the authors also underline somecritical aspects that have to be more investigated.